Generalized Bullous Fixed Drug Eruption Associated with Allopurinol: A Case Report - Anselma Dyah Kartika Hadi; Cagar Irwin Taufan Pamungkas; Asri Ayu Firdausi; Agnellia Maulidya Utami (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2026)
Background: Generalized Bullous Fixed Drug Eruption (GBFDE) is an uncommon type of FDE and is defined as typical FDE lesions accompanied by widespread bullous and skin erosions that is often confused with SJS-TEN due to their similarity in clinical characteristics. Case: A 59-year-old man was presented to the ER with generalized erythematous lesions associated with pain and itchy sensations, and followed by the appearance of bullae after taking allopurinol. He has a previous history of similar erythematous lesions, which he recovered spontaneously 5 months ago. The medical history and clinical presentation inform the clinical diagnosis of GBFDE. He was treated with systemic and topical corticosteroids and antihistamines. He showed clinical improvement during his hospital stay. He was discharged after 5 days of hospitalization with hyperpigmentation lesions. Discussion: GBFDE has clinical features that can mimic SJS-TEN. Despite the significant overlap in clinical features, one can still make some distinctions. Hence, medical history and clinical presentation are crucial to distinguish GBFDE from SJS/TEN. In this case, allopurinol is the culprit medication. The appropriate management of GBFDE is discontinuation of the causative medication and supportive treatment. Performing a careful anamnesis and physical examination is important to distinguish between GBFDE and SJS-TEN. Early identification and discontinuation of the causative drug can help to improve outcomes and prevent future exposure to the same drug.